The importance of understanding attachment and resilience in residential child care: an argument against risk-averse practice - Kathy Grant (Scottish Journal of Residential Child Care)
The intent of this paper is to explore the importance of relationships within Scottish residential child care settings. Whilst making reference to research, theoretical and legislative material, consideration will be given to the ethical and developmental issues surrounding the risk-averse approach to practice believed to be increasingly evident in relation to care provision within contemporary social work in Scotland (Scottish Executive, 2005). With reference to this, I will provide a critical analysis of the way in which riskaverse practice has infiltrated into residential child care practice in relation to meeting the attachment needs and promoting resilience of the looked after and accommodated children and young people to whom they provide a service.